ANGGREK DEWATA: PENDAMPINGAN AGRIBISNIS JERUK SIAM DESA AIR TALAS, KECAMATAN RAMBANG NIRU, KABUPATEN MUARA ENIM, SUMATERA SELATAN - Wilujeng, Catherine Wahyuning; Prayoga, Dedo Kevin (Transpublika Publisher, 2023)
The cultivation and marketing assistance program for Siam oranges in Air Talas Village, Rambang Niru District, Muara Enim Regency, South Sumatra, aims to increase the production and marketing of Siam oranges and diversify the product range. This program involves training in the use of organic fertilizers, plant disease control, and the development of derivative products such as jam, pie, and orange syrup. Additionally, the program also includes innovation development through the use of the Trichoderma fungicide to address the current threat of Citrus Vein Phloem Degeneration (CVPD) disease. The program is expected to enhance farmers' income, strengthen the local economy, and empower the community of Air Talas Village.